The enamel thickness of gestational diabetes mellitus rat offspring - Nurdiana Dewi; Ahmad Syaify; Ivan A. Wahyudi (DiscoverSys Inc., 2021)
Objective: To determine the molar enamel thickness of rat offsprings born to diabetic rat.Material and Methods: This research used sixteen rat offsprings born to 8 diabetic rats who had been injected with STZ dose of 40 mg / kg and 16 rat offsprings born to 8 control rats. Rat offsprings were decapitated on day 5 after birth and taken right mandibular molar tooth germ. Tooth germ then embedded in paraffin block. Haematoxylin eosin staining performed for histological analysis. Enamel thickness measured on the images using ImageJ Software at 5 field of view.Results: The enamel thickness on the Diabetes Mellitus (DM) group (333.02 ± 135.81 µm) were lower than control group (415.39 ± 146.17 µm). Mann Whitney test results showed a significant difference between the DM and control group.Conclusion: It was concluded that enamel thickness decreases in gestational diabetes mellitus rat offspring.